The Effectiveness of of the Collaborative and Individual Gamification Method on the Math Performance of Third Grade Elementary School Students - Marzieh Abbaspoor; Marzieh Dehghani; Mohammad Javadipour; Ebrahim Khodaie (پژوهش‌های کاربردی روانشناختی)
The purpose of this research is to investigate the effect of gamification on the performance of the third grade of elementary school mathematics. One of the lessons that have always been associated with many challenges in the educational system is mathematics, and these challenges must be solved. One of the teaching methods is using gamification. The research method is semi-experimental with pre-test-post-test with control group. The statistical population of this research is all the students of the third grade of Tehran primary school in the academic year 1401-1402. 60 students with math disorders were randomly divided into three experimental groups: individual, cooperative and control. The students with learning disorders in the experimental group were trained with gamification method for 12 sessions. But the control group participated in the meetings with the traditional method. The data obtained from the pre-test and post-test were analyzed using covariance analysis. The findings showed that the use of this method has led to an improvement in the performance of third grade elementary school students in mathematics. But there is no significant difference between individual and cooperative group.